Analysis Correlation Between Learning Interest and Learning Difficulties with Learning Outcomes of Junior High School Students In Padang - Ririn Indria Sari; Ramadhan Sumarmin; Resti Fevria; Ganda Hijrah Selaras (ATRIUM PENDIDIKAN BIOLOGI, 2019)
The learning process has a benchmark that refers to the achievements experienced by students, namely learning outcomes. Learning outcomes achieved by students have two influencing factors namely internal and external factors. These two factors that influence learning outcomes are interest and learning difficulties. The results of observations on the learning outcomes of students of SMPN 11 Padang in science are still low. Students say that science learning are numerous and difficult. The existence of students who score below the average and the lack of student interest shows the student's interest in learning in science is less and it can be assumed that students have difficulty learning science. Research is a descriptive study. Research uses a correlational study approach. Research subjects consisted of 30 people in class VIII G of SMP 11 Padang. To find out the relationship between variables expressed by the correlation coefficient, data analysis techniques are used using the Sperman Rank correlation. The correlation between student interest and learning outcomes is weak, that is -0.32, the contribution of 10.24% does not have a significant relationship. There is a significant relationship between learning difficulties and learning outcomes, medium criteria w ith a value of 0.59, contribution value is 34.81%. Correlation criteria for interests and difficulties with strong learning outcomes with a value of 0.66 and a contribution of 43.56%, as well as a significant relationship between variables. The results of the relationship between learning interest and learning difficulties with learning outcomes are strong and each variable has a significantly relationship.